2014
DOI: 10.1007/s00442-014-3126-0
|View full text |Cite
|
Sign up to set email alerts
|

Height-related changes in leaf photosynthetic traits in diverse Bornean tropical rain forest trees

Abstract: Knowledge of variations in morphophysiological leaf traits with forest height is essential for quantifying carbon and water fluxes from forest ecosystems. Here, we examined changes in leaf traits with forest height in diverse tree species and their role in environmental acclimation in a tropical rain forest in Borneo that does not experience dry spells. Height-related changes in leaf physiological and morphological traits [e.g., maximum photosynthetic rate (Amax), stomatal conductance (gs), dark respiration ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
84
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(105 citation statements)
references
References 71 publications
16
84
1
3
Order By: Relevance
“…Weak correlations between Pn and leaf N were observed by other authors (e.g. Kenzo et al, 2015). In the present experiment, it is likely that the optimal nutrient availability in the root allowed plants taking up the needed quantity of nutrients to support the higher growth rate induced in treated plants, without affecting leaf N content (Table 4).…”
Section: Discussioncontrasting
confidence: 66%
“…Weak correlations between Pn and leaf N were observed by other authors (e.g. Kenzo et al, 2015). In the present experiment, it is likely that the optimal nutrient availability in the root allowed plants taking up the needed quantity of nutrients to support the higher growth rate induced in treated plants, without affecting leaf N content (Table 4).…”
Section: Discussioncontrasting
confidence: 66%
“…The upper canopy environment with high photosynthetic productivity may allow symbiosis with EcM fungi, which may have a higher carbohydrate demand than AM fungi (de Kroon and Visser 2003;Smith and Read 2008). In fact, dominant dipterocarp trees in the emergent layer showed higher photosynthetic ability under upper canopy conditions than most non-dipterocarp trees or lower trees when they were in the emergent layer (Kenzo et al 2015b;Inoue et al 2015). Canopy, sub-canopy, and understory species showed significantly negative leaf d 15 N values, with large variation.…”
Section: Effect Of N Isotope Discrimination By Root Mycorrhizal Fungimentioning
confidence: 93%
“…The monthly mean temperature varied only slightly, from 25.6°C in February to 27.0°C in May (Kenzo et al 2007). The mean canopy height in the stand was about 30-40 m; some emergent trees reached 50 m in height (Kenzo et al 2015b). …”
Section: Study Sitesmentioning
confidence: 98%
“…Moreover, large interannual variations of rainfall in Cambodia may cause strong drought stress for DEF trees because exceptional leaf shedding occurs in evergreen canopy trees during the dry season in years of extremely low rainfall (Iida et al 2013). Trees in DEF with high wood density may afford high tolerance to drought stress with low stem water potential by having high physical strength with thick cell walls during the dry season (Holbrook et al 1995, Onoda et al 2010, especially in tall canopy trees with large gravity potential (Kenzo et al 2015, Ryan et al 2006. Several researchers also found that tree species in canopy gaps were classified independently (canopy gap species) in DEF, although we did not categorize gap species for trees in DDF due to an unclosed forest canopy in the forest type (Fig.…”
Section: Categories Of Tree Life-formsmentioning
confidence: 99%